NUTRITIONAL PROFILE AND INFLAMMATORY STATUS OF STABLE CHRONIC HEMODIALYSIS PATIENTS AT NEPHROLOGY DEPARTMENT, MILITARY HOSPITAL RAWALPINDI - Siddiqui, Umair Ahmed; Halim, Abdul; Hussain, Tassawar (Journal of Ayub Medical College Abbottabad, 2007)
Background: Protein-energy malnutrition (PEM) is common in the haemodialysis population. Identification and management of these patients can result in significant reduction in morbidity and mortality. Aim of the study was to find the prevalence of PEM in otherwise stable haemodialysis patients at Military Hospital Rawalpindi at a single point in time with the help of established biochemical and physical markers. Material and Methods: Height, dry weight and body mass index (BMI) were recorded for 64, stable, 14-75 year-old patients who were on haemodialysis for ï‚³3 months. Blood samples were drawn (pre-dialysis) for complete blood count, serum C-reactive protein, serum total protein, serum albumin and serum Creatinine. Ideal body weights and BMI were obtained from Pakistan Army Selection and Recruitment standards. Results: Out of 64 patients 43 (67%) were males. Mean age was 44.5ï‚±14.3 yr. Mean haemoglobin was 8.84ï‚±2 g/dl. Fifty-seven patients (89%) had haemoglobin ï‚£11 g/dl. Pearson correlation coefficient (r) with albumin was significant (p=0.01). The mean serum albumin was 34.2ï‚±4.25 g/l. Serum albumin of less than 40 g/l in 58 patients (90.6%). C-Reactive protein was available for 58 (90.6%) of patients. It was positive in 23 (35.9%) and was associated with a lower mean serum albumin (32.7 g/l vs 35.4 g/l) which was statistically significant (p=0.017). There was no significant relationship between the lymphocyte count and albumin levels. However, the Pearson correlation of albumin with the total WBC count gave a p value of 0.05. Mean BMI was 19.8ï‚±2.9 kg/m2. Thirty-seven (57.8%) patients had BMI in the normal range (18.5-24.6 kg/m2) and 24 (37.5%) were below normal (14.6-18.3 kg/m2). Correlation of albumin with BMI and serum creatinine was not significant (p= 0.46 and 0.53 respectively). Conclusion: Serum albumin is a strong marker of malnutrition but needs to be associated with other physical and inflammatory parameters to correctly identify malnourished haemodialysis patients. Key Words: Haemodialysis; nutrition; albumin; C-reactive protein; body mass index